2020
DOI: 10.1155/2020/7294820
|View full text |Cite
|
Sign up to set email alerts
|

Pedaling Performance Changing of Elite Cyclists Is Mainly Determined by the Fatigue of Hamstring and Vastus Muscles during Repeated Sprint Cycling Exercise

Abstract: Repeated sprint cycling is an effective training method in promoting athletic performance of cyclists, which may induce severe fatigue of lower limb muscles. However, the relationship between the fatigue of each lower limb muscles and the changing of exercise performance remains unclear. In this study, ten cyclist volunteers performed a series of 6-second sprints with 24-s recovery for five times. Power, cadence, and EMG mean frequency (MNF) of each lower limb muscle group for every 2-second epoch, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This improved metabolic efficiency in the extensor muscles is presumed to be a result of their interaction with the gluteal muscles, particularly the gluteus maximus [ 29 ]. Additionally, Wang et al reported that fatigue in the hamstrings and vastus medialis significantly affects cycling performance [ 32 ]. Particularly at high speeds, the activity of the hamstring muscles is increased.…”
Section: Discussionmentioning
confidence: 99%
“…This improved metabolic efficiency in the extensor muscles is presumed to be a result of their interaction with the gluteal muscles, particularly the gluteus maximus [ 29 ]. Additionally, Wang et al reported that fatigue in the hamstrings and vastus medialis significantly affects cycling performance [ 32 ]. Particularly at high speeds, the activity of the hamstring muscles is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the calculated F/v and P/v profiles appear to predominantly reflect the muscle with the lowest aerobic capacity and the highest glycolytic power, requiring the recruitment of larger motor units at a given work rate. This idea is supported by the research of Wang et al (2020), according to which the contribution of the vastus lateralis muscle, which has the highest proportion of fast-twitch glycolytic fibers among the propulsive muscles in cycling, significantly determines the performance of elite cyclists.…”
Section: Limitationsmentioning
confidence: 96%
“…There are also changes in the muscle articulation angle and the neural activation pattern, recorded in the EMG signal [3,4]. More details of muscle fatigue with dynamic contractions are presented in [12][13][14].…”
Section: Introductionmentioning
confidence: 99%